2022
DOI: 10.1101/2022.06.10.495672
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genome-wide association and genomic prediction of growth traits in the European flat oyster (Ostrea edulis)

Abstract: The European flat oyster (Ostrea edulis) is a bivalve mollusc that was once widely distributed in Europe and represented an important food resource for humans for centuries. Populations of O. edulis experienced a severe decline across their biogeographic range mainly due to anthropogenic activities and disease outbreaks. To restore the economic and ecological benefits of European flat oyster populations, extensive protection and restoration efforts are in place within Europe. In line with the increasing intere… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 96 publications
1
5
0
Order By: Relevance
“…With the panels containing 300 or 500 SNPs, the accuracy was within the range of those obtained with PBLUP, with a non-significant decrease in accuracy by 3.3% or 1.6% for the 300-SNP panels for RandLD and EquaLD, respectively (see Additional file 1: Table S3). Those values are within the range of what has been reported in several other aquaculture species for various traits [17,18,20,26,29,32,[52][53][54][55].…”
Section: Performance Of the Ld Panelssupporting
confidence: 88%
See 2 more Smart Citations
“…With the panels containing 300 or 500 SNPs, the accuracy was within the range of those obtained with PBLUP, with a non-significant decrease in accuracy by 3.3% or 1.6% for the 300-SNP panels for RandLD and EquaLD, respectively (see Additional file 1: Table S3). Those values are within the range of what has been reported in several other aquaculture species for various traits [17,18,20,26,29,32,[52][53][54][55].…”
Section: Performance Of the Ld Panelssupporting
confidence: 88%
“…Two in silico studies on five fish species (common carp, turbot, sea bass, rainbow trout and Atlantic salmon) [17,18] compared LD panels to HD panels with a density ranging between 12 to 40K and found that LD panels containing between 3000 and 10,000 SNPs are sufficient to obtain near maximum accuracy. Recently similar prediction accuracies with 2000 SNPs and 4500 SNPs were obtained in flat oyster [20]. For European sea bass and sea bream populations, which were initially genotyped with about 60K SNPs, the use of a panel with only 6000 SNPs achieved accuracies that reached 90% of the accuracy of the HD panel [19].…”
Section: Performance Of the Ld Panelsmentioning
confidence: 52%
See 1 more Smart Citation
“…In this regard, the genome reported here is proving useful already, with a recent study revealing that SNP markers previously associated with Bonamia resistance (Vera et al, 2019) are located in high linkage-disequilibrium across a large region of super-scaffold 8, which contains many candidate immune genes (Martinez et al 2022). Another recent study from has mapped variants genotyped with an existing medium density SNP array (Gutierrez et al, 2017) against our new O. edulis genome, identifying QTLs underpinning variation in growth traits on super-scaffold 4 (Peñaloza et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The ML algorithms learn the details using the training dataset, and its prediction efficiency is evaluated using the validation dataset. A derivation of this method called fivefold cross-validation analysis is now increasingly used in genomic prediction analyses of Portuguese oysters (Vu et al, 2021c), European flat oysters (Peñaloza et al, 2022), and Pacific oysters (Kriaridou et al, 2023). Typically, the genotype data is divided into 80% training and 20% validation datasets.…”
Section: Machine Learning Methods For Optimisation Of Genomic Selecti...mentioning
confidence: 99%